Cold-induced urticaria with a familial transmission: a case report and review of the literature - Furr, Joe C (BioMed Central, 2012)
INTRODUCTION: Cryopyrin-associated periodic syndrome is a rare genetic disorder causing cold-induced urticaria, severe arthralgias, and (potentially) renal failure and hearing loss. Therapies that effectively control the symptoms and prevent the complications of this debilitating disorder are now available, making recognition of this disease important. CASE PRESENTATION: A 60-year-old Caucasian woman presented with complaints of rash and joint pains to a general medicine clinic. Her history showed that her symptoms were linked to cold exposure, but the results of a cold stimulation time test were negative. Several generations of her family had similar symptoms. CONCLUSIONS: This case highlights the importance of considering cryopyrin-associated periodic syndrome in the differential diagnosis of cold-induced urticaria. Several medications targeting interleukin-1-beta are available, providing significant relief from symptoms and improvement in quality of life in affected patients.